The role of ‘educated native speakers’ in providing language analysis for the determination of the origin of asylum seekers - Fraser, Helen (International Journal of Speech, Language and the Law, 2009)
This paper speaks to a debate which has arisen across various branches of linguistics (see Eades, 2009) regarding the relative levels of responsibility that should be given to (a) qualified linguists with professional expertise in a particular language, and (b) ‘educated native speakers’ of the language, in conducting Language Analysis for the Determination of the regional or social Origin of asylum seekers (LADO). It reviews existing evidence from the phonetic and sociolinguistic literature regarding the reliability of accent judgments by linguists and non-linguists. It argues that, while LADO is a valid form of assistance to offer in the asylum process, careful evaluation of its limitations, in general and in specific cases, is crucial - ,as in other branches of forensic linguistics. The paper concludes by calling for (a) a proper research program to investigate people’s actual abilities in recognising, discriminating and identifying accents under various sociolinguistic conditions; (b) collaboration between LADO agencies and linguists to develop analysis and testing procedures; and (c) a system of accreditation by an independent, international authority for the agencies that carry out LADO.